30 Remember me: support through remembrance during the COVID19 pandemic. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Pryce, Ruth; Morris, Rachel; Stanley, Sarah
Abstract : Background: The COVID19 pandemic has highlighted a greater need for spiritual support and remembrance in a difficult time when usual comforts associated with end of life care have been stripped away. Marie Curie Hospice Liverpool have worked to develop unique ways to continue support through spiritual care and remembrance using technology and links to our local communities. Methods: There have been many challenges throughout the pandemic including the closure of the hospice to visitors, meaning for patients that face to face contact with relatives or their own faith leaders was no longer possible. Our chaplain continues to provide spiritual care for patients and carers, whilst creating remembrance opportunities. Embracing technology and the support of the local community has been vital in enabling patients to receive the best possible spiritual care. An example of this is the engagement of local church groups supporting the hospice by providing knitted hearts to keep patients and relatives connected. Remembrance opportunities have been created, including: online memorial services, use of technology to allow patients and families to come together for prayer, weekly email reflections to support staff wellbeing, and developing the chapel into an 'escape room' providing space for reflection during difficult times. Results: Results are positive. Patients and carers report feeling supported spiritually in a difficult time, which has been essential to their care. Remembrance work via online platforms has allowed our hospice and local community to be supported through bereavement and feedback from carers, local community groups and staff has been positive and complimentary. Conclusions: Our work has demonstrated that despite the challenges presented during the pandemic, spiritual care and remembrance continues to provide comfort to those affected. Developing unique ways to continue supporting people has proven to be successful. Work is ongoing. We are eager to innovate and continue providing support in these difficult times.